2006
DOI: 10.1111/j.1530-0277.2006.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atypical Anxiolytic N‐Phenyl‐2‐[1‐[3‐(2‐Pyridinylethynyl)Benzoyl]‐4‐Piperidine]Acetamide (JNJ‐5234801) on Alcohol Intake in Alcohol‐Preferring P Rats

Abstract: The novel atypical anxiolytic JNJ-5234801 has a favorable profile effects on alcohol intake and related measures compared with naltrexone, which is recommended for the treatment of alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Although the subchronic administration of sazetidine-A significantly reduced alcohol intake and preference initially, partial tolerance developed after the seventh treatment. We and others previously have shown that tolerance also develops with repeated administration of naltrexone and naloxone (Rezvani et al 2007; Cowen et al 1999; Overstreet et al 1999). Presently, it is not clear if the observed partial tolerance is the consequence of the central nicotinic receptor modification or is of pharmacokinetic nature.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although the subchronic administration of sazetidine-A significantly reduced alcohol intake and preference initially, partial tolerance developed after the seventh treatment. We and others previously have shown that tolerance also develops with repeated administration of naltrexone and naloxone (Rezvani et al 2007; Cowen et al 1999; Overstreet et al 1999). Presently, it is not clear if the observed partial tolerance is the consequence of the central nicotinic receptor modification or is of pharmacokinetic nature.…”
Section: Discussionmentioning
confidence: 85%
“…P rats, in addition to high preference for alcohol (Li et al 1993; Rezvani et al 2007, 2009), recently have been shown to have higher rates of nicotine self-administration compared with their alcohol-non-preferring counterpart, NP rats (Lê et al 2006). It was hypothesized that sazetidine-A, by desensitizing α4β2 nAChRs, would significantly reduce both alcohol and nicotine intake in P rats.…”
Section: Introductionmentioning
confidence: 99%
“…Another difference between NAL and LY was that 1 mg/kg NAL lost effectiveness on the fourth day of treatment, whereas 0.1 mg/kg LY maintained its effectiveness. P rats have shown the development of tolerance to the effect of NAL over days (Rezvani et al, 2007; Sable et al, 2006). On the whole, the results indicate that the opioid receptor system is involved in maintaining alcohol consumption and self-administration behaviors in both limited and free-access procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinically, naltrexone (NAL), an opioid receptor subtype nonspecific antagonist, has been shown to decrease alcohol consumption in nonhuman primates (Boyle et al, 1998; Kornet et al, 1991; Myers et al, 1986; Williams et al, 1998), in rat lines selectively bred for high-alcohol consumption (Gilpin et al, 2008; Koistinen et al, 2001; Rezvani et al, 2007; Sabino et al, 2006; Sable et al, 2006; Zalewska-Kaszubska et al, 2008), in rat lines selectively bred for characteristics other than alcohol consumption (Pellicano and Sadile, 2006), in nonselected genetically heterogenous rats (Czachowski and Delory, 2009; Ji et al, 2008; Kiefer et al, 2005; Kuzmin et al, 2008; Mhatre et al, 2004; Oliva and Manzanares, 2007; Walker and Koob, 2008), and in inbred C57BL/6J (B6) mice (Escher and Mittleman, 2006; Grahame et al, 2000; Kamdar et al, 2007; Kim et al, 2004). Among most double-blind controlled clinical trials, NAL has demonstrated a consistent yet modest effect in reducing heavy alcohol consumption in both alcohol-dependent (Assanangkornchai and Srisurapanont, 2007; Krishnan-Sarin et al, 2007; Pettinati et al, 2006) and nondependent (Tidey et al, 2008) individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This particular strain of alcohol-drinking rat has been characterized and widely used to study the effects of different compounds on voluntary alcohol consumption (Overstreet et al 1999). Alcohol intake was determined using the standard two-bottle choice method as previously described (Rezvani et al 2007(Rezvani et al , 2000(Rezvani et al , 2009(Rezvani et al , 2010. Briefly, after establishment of a reliable baseline for alcohol and water intake, rats were administered systemically (subcutaneously) in the morning (10:00 am) either with the vehicle (20% (w/v) cyclodextrin), or one of the three doses of JNJ-39220675 (0.3, 3, and 10 mg/kg) or naltrexone (as a positive control, 5 mg/kg, s.c.).…”
Section: Jnjmentioning
confidence: 99%